1999
DOI: 10.1104/pp.119.4.1517
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroid/Sterol Synthesis and Plant Growth as Affected bylka and lkb Mutations of Pea1

Abstract: The dwarf pea (Pisum sativum) mutants lka and lkb are brassinosteroid (BR) insensitive and deficient, respectively. The dwarf phenotype of the lkb mutant was rescued to wild type by exogenous application of brassinolide and its biosynthetic precursors. Gas chromatography-mass spectrometry analysis of the endogenous sterols in this mutant revealed that it accumulates 24-methylenecholesterol and isofucosterol but is deficient in their hydrogenated products, campesterol and sitosterol. Feeding experiments using 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
83
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 58 publications
6
83
1
Order By: Relevance
“…This is in contrast with what is observed in BR biosynthetic mutants, in which the blockage of a specific reaction leads to the significant accumulation of intermediate species prior to the reaction step (Hong et al, 2002(Hong et al, , 2003Tanabe et al, 2005). Previous studies showed that BR signaling mutants, which included bri1 d61, accumulate high levels of all the BR intermediates Nomura et al, 1999;Yamamuro et al, 2000); however, endogenous BR levels were lower in ravl1-1 mutants when compared with wild-type plants, even if the expression of BRI1 was severely repressed. This may be a consequence of the inactivation of BR biosynthetic genes in ravl1-1 plants.…”
Section: Ravl1 Is Necessary For Maintenance Of Br Homeostasiscontrasting
confidence: 51%
“…This is in contrast with what is observed in BR biosynthetic mutants, in which the blockage of a specific reaction leads to the significant accumulation of intermediate species prior to the reaction step (Hong et al, 2002(Hong et al, , 2003Tanabe et al, 2005). Previous studies showed that BR signaling mutants, which included bri1 d61, accumulate high levels of all the BR intermediates Nomura et al, 1999;Yamamuro et al, 2000); however, endogenous BR levels were lower in ravl1-1 mutants when compared with wild-type plants, even if the expression of BRI1 was severely repressed. This may be a consequence of the inactivation of BR biosynthetic genes in ravl1-1 plants.…”
Section: Ravl1 Is Necessary For Maintenance Of Br Homeostasiscontrasting
confidence: 51%
“…In Arabidopsis, 6-DeoxoBRs are more active than 6-OxoBRs in the light, whereas in the dark 6-DeoxoBRs are less active (Fujioka et al, 1997;Choe et al, 1998). In tomato, however, 6-DeoxoBRs are more active than 6-OxoBRs both in the light and in the dark (Koka et al, 2000), and in pea, 6-OxoBRs are more active than 6-DeoxoBRs in the light (Nomura et al, 1999). These results have suggested that activities of exogenously supplied BRs are modulated by intracellular BR synthetic activity, which varies among tissues and under light conditions.…”
Section: -Deoxobrs Are As Active As 6-oxobrs In the Zinnia Systemmentioning
confidence: 57%
“…However, the predominance of either pathway varies among plant species and among tissues. For instance, both the late and early C6-oxidation pathways occur in pea (Nomura et al, 1999) and Arabidopsis (Fujioka et al, 1997), whereas the late C6-oxidation pathway is predominant in tomato (Bishop et al, 1999).…”
mentioning
confidence: 99%
“…Such regulation seems to be cancelled in BR-insensitive mutants because CS accumulates at aberrant levels in pea lka (Nomura et al, , 1999 and tomato curl-3 (T. Nomura, T. Yokota, and G.J. Bishop, unpublished data).…”
mentioning
confidence: 99%
“…Many of these mutants also have darkgreen leaves, reduced fertility, a prolonged lifespan, and display abnormal skotomorphogenesis. BRinsensitive mutants have been identified in Arabidopsis, pea, tomato, and rice (Oryza sativa; Clouse et al, 1996;Kauschmann et al, 1996;Li and Chory 1997;Nomura et al, 1999;Koka et al, 2000;Yamamuro et al, 2000).…”
mentioning
confidence: 99%